Integrated Framework for Identification of Polluted Zones in Coastal Areas of Thiruvallur District of Tamil Nadu (India) - Kishan Singh Rawat (Faculty of Geography, Universitas Gadjah Mada, 2019)
In this research work, hydro-geochemical characteristics were determined from twenty groundwater samples and classified into water quality zones on the basis of the World Health Organization (WHO 2006) using inverse distance weighted interpolation technique. Groundwater samples were analyzed with respect to calcium (Ca2+), magnesium (Mg2+), sodium (Na+), HCO3, total nitrate (NO2+NO3ˉ), chloride (Cl−), sulphate (SO42−), total dissolved solids (TDS), hydrogen ion concentration (pH) and electrical conductivity (EC) were measured form groundwater samples. The water quality indices (WQI1 and NPI = WQI2) were used to categorize the water. Water Quality Index (WQI) value suggest that the 65% groundwater samples (excellent + good) are safe for drinking uses and 35% groundwater samples (very poor + poor) needs treatment before consumptive uses from WQI1. Further, NPI (WQI2), shows 40% and 60% of groundwater falls under good and poor condition respectively. The findings highlight that the groundwater of few areas requires some degree of treatment before consumptive uses.